Protein and mRNA expression of estradiol receptors during estrus in yaks (Bos grunniens) - Shengdong Huo; Qijian Yuan; Taojie Zhang; Junlin Liu; Ayimuguli Abudureyimu; Jutian Yang (Revista Brasileira de Zootecnia, 2015)
ABSTRACTThe objective of this study was to investigate mRNA by real-time PCR and protein expression by immunofluorescence of the estradiol receptors (ER) in the pineal gland, hypothalamus, pituitary gland, and gonads of yaks (Bos grunniens). The analysis showed that the level of expression of ER mRNA was greater in the pituitary gland tissue than in other glands during estrus. Immunofluorescence analyses showed that ER proteins were located in the pineal cells, synaptic ribbon, and synaptic spherules of the pineal gland. In the hypothalamus, ER proteins were located in the magnocellular and parvocellular neurons. The ER proteins were located in acidophilic cells and basophilic cells in the pituitary gland. In the ovary, ER proteins were present in the ovarian follicle, corpus luteum and Leydig cells. Estradiol exerts its main effects on the pituitary gland during estrus in yak.